2023
DOI: 10.1021/acssuschemeng.2c07136
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Assessment of Large-Scale Green Hydrogen Logistics Using Ammonia As Hydrogen Carrier: Comparison to Liquified Hydrogen Distribution and In Situ Production

Abstract: Green hydrogen plays a key role in decarbonizing the economy. However, the best conditions for producing it are often far from consumption places. This work compares three alternatives for large-scale green hydrogen distribution based on the levelized cost of hydrogen (LCOH): the use of green ammonia as a hydrogen carrier, the use of liquid hydrogen, and on-site production. All of the alternatives include production, packing, transport, and unpacking of hydrogen. Results show that liquid hydrogen outperforms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…7 Compared to liquid H 2 , which needs to be stored at −253 °C, liquid NH 3 can be stored at 20 °C and 8 bar and has 1.7-fold higher H 2 storage density (120.3 vs. 70.9 kg H 2 m −3 ), thus drawing considerable attention. 8,9 The infrastructure for NH 3 production, storage, and transportation is well-established because this compound has long been used as a refrigerant gas and material for fertilizer production. 10 In addition, NH 3 decomposition (2NH 3 (g) ⇋ N 2 (g) + 3H 2 (g), Δ H ° = 46.22 kJ mol −1 ) generates no greenhouse gases and is therefore an eco-friendly H 2 production process.…”
Section: Introductionmentioning
confidence: 99%
“…7 Compared to liquid H 2 , which needs to be stored at −253 °C, liquid NH 3 can be stored at 20 °C and 8 bar and has 1.7-fold higher H 2 storage density (120.3 vs. 70.9 kg H 2 m −3 ), thus drawing considerable attention. 8,9 The infrastructure for NH 3 production, storage, and transportation is well-established because this compound has long been used as a refrigerant gas and material for fertilizer production. 10 In addition, NH 3 decomposition (2NH 3 (g) ⇋ N 2 (g) + 3H 2 (g), Δ H ° = 46.22 kJ mol −1 ) generates no greenhouse gases and is therefore an eco-friendly H 2 production process.…”
Section: Introductionmentioning
confidence: 99%
“…Greenhouse gases (GHGs) produced through burning fossil fuels have an adverse impact on both the environment and society. , Hydrogen is an eco-friendly energy source that rivals fossil fuels in terms of its heating value. As part of the efforts to find sustainable alternatives to gray syngas production that emit extensive GHGs and meet current and future demand for syngas, Hilliard conducted an economic analysis of green hydrogen technology and demonstrated that it is the most promising option in the distant future due to its current extensive energy provisions, and recent trends revealed considerably greater costs than methane reforming technologies. Villalba-Herreros et al conducted a technoeconomic study of large-scale production of green hydrogen, concluding that blue hydrogen had levelized costs 60% lower than those of green hydrogen production …”
Section: Introductionmentioning
confidence: 99%